Prospective Study of Radiological and Functional Outcome of Closed Subtrochanteric Fracture Fixation with Proximal Humerus Interlocking Plate in Adolescent Patients (Global Journal of Medical Research, 2020)
Abstract not found
Keywords: subtrochanteric fracture; proximal humerus locking plate; adolescent patients